Results of 2003 Early, Mid and Full Season, and Roundup Ready Cotton Variety Tests in Florida - David L. Wright; P. J. Wiatrak; James J. Marois; B. Kidd (EDIS)
Cotton was planted with a cone planter at the seeding rate of 85 seeds/20 ft of row with 36” row spacing on 5 May, 2003 after strip tilling into tilled small grain cover crops. Thimet 20 G was applied in furrow at 6.5 lb/A. This document is SS-AGR-222, a publication of the Agronomy Department, Florida Cooperative Extension Services, Institute of Food and Agricultural Sciences, Univeristy of Florida. Publication date April 2004.